Strategi Pembelajaran Kelas Homogen Pada Pesantren - M. Yusuf (Prodi Manajemen Pendidikan Islam STAI Darussalam, 2021)
The study of learning strategies in pesantren seems endless, every time it is researched, it will bring up new and different views and perspectives, as well as when changing objects between one pesantren and another, it will bring up various conclusions, although the same in style and character. . The uniqueness and diversity in maintaining the characteristics of each pesantren are the main reasons why pesantren are exclusive and different from other types of educational institutions, including the classroom learning strategies that apply homogeneous classes. The majority of Islamic boarding schools in Indonesia apply the same thing, namely learning in class by differentiating students by gender, this is what triggers various assumptions about homogeneous class goals and objectives, the learning strategies that are implemented and how they impact learning motivation, communication, social behavior and character learners. The method used in this research is a research library which relies on various references to support this research activity. The conclusion is that the aim of enforcing a homogeneous class in pesantren is that apart from the tradition of the pesantren, the culture of the pesantren minimizes the mingling of men and women who are not Muslim. The learning strategy is applied in a homogeneous class based on learning motivation, communication, social behavior / self-confidence and the character of students. The impact is that motivation to learn in a homogeneous class has no impact. Meanwhile, communication is only visible when engaging in society, while the social maturity of students in a homogeneous class is lower than that of heterogeneous class as for the characters of male and female students, there is a difference, a different learning strategy is needed.